Tools for Measuring Clinical Ultrasound Competency: Recommendations From the Ultrasound Competency Work Group. (30th July 2019) - Damewood, Sara C.; Leo, Megan; Bailitz, John; Gottlieb, Michael; Liu, Rachel; Hoffmann, Beatrice; Gaspari, Romolo J.
Abstract: Competency in clinical ultrasound is essential to ensuring safe patient care. Competency in clinical ultrasound includes identifying when to perform a clinical ultrasound, performing the technical skills required for ultrasound image acquisition, accurately interpreting ultrasound images, and incorporating sonographic findings into clinical practice. In this concept paper, we discuss the advantages and limitations of existing tools to measure ultrasound competency. We propose strategies and future directions for assessing competency in clinical ultrasound.